Classification of zinc hydrolases using a sequence-based phylogenetic method / Nur Syamim Ismail - Ismail, Nur Syamim (2014)
There are many methods in classifying proteins. Some classify proteins manually; some classify proteins using computational method whereas some classify proteins by combining both methods. In this research, the result of protein classifications using sequence-based phylogenetic method is compared with manual method and a previous work of classifying proteins. The objectives of this research are to assess the similarities of sequence-based phylogenetic tree base on the sequence alignment method; to construct a phylogenetic tree using similarity values from protein alignment; and to validate the phylogenetic tree against standard protein classifications. The dataset is obtained from Protein Data Bank (PDB) and the proteins sequences are aligned together using CLUSTALW. Then, a sequence-based phylogenetic tree is constructed and validated using PHYLIP. The final result is compared with the structure-based phylogenetic tree and a previous work of protein classifications. The results show that the sequence-based phylogenetic tree is more accurate in classifying proteins with high similarities. However, the sequence-based phylogenetic tree is less accurate in determining the proteins with low sequence similarities. As conclusion, sequence-based phylogenetic tree produced from this study is reliable in representing the proteins that have high sequence similarities.